Regulatory legal provisions of the public control at state customs - Вишновецький, Вадим Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The problem of legal ensuring of the public control at state customs is explored in the article. The system of legal acts that regulate relations regarding public control at state customs is determined. The author also gives propositions concerning the ways of its improvement. Ukraine has a sufficiently extensive, hierarchically structured system of legal acts, which provides an opportunity for the public to participate in the implementation of public control at state customs. This system is mainly formed by laws and regulations that have a general character and regulate relations that arise while public control performance and are not limited by any departmental frames of a certain state body. With the purpose of resolving the differences concerning the definition of subjects, that cooperate with the organs of State Fiscal Service of Ukraine, in legal acts, the author offers to make an amendment to the art. 562 of Customs Code of Ukraine: to add associations of citizens, civil society organizations, trade unions and employers' organizations, and also enterprises, institutions and organizations to the list of subjects of interaction.